Seven new species of Perlomyia (Plecoptera: Leuctridae) from Japan - Sivec, Ignac (Illiesia, 2012)
Seven new species of Perlomyia are described from specimens collected in Iwate Prefecture and Nara Prefecture, Honshu, Japan. A key to the Japanese male Perlomyia (P. gifuensis Kohno excluded), and a checklist for 18 currently recognized species are presented. Perlomyia nipponica (Okamoto) is placed as a nomen dubium.
Keywords: entomology; Perlomyia; Plecoptera; Leuctridae; new species; Japan